Medical experience of family members of children in pediatric infusion room: a cross-sectional survey - Zhao, Dan; Liu, Yong; Zhang, Jing; Wang, Yan; Chen, Dan (Frontiers in Pediatrics, 2025)
BackgroundEnhancing the medical experience of children and their family members constitutes a crucial component of clinical management. This study aims to analyze the current status of the medical experience among family members of children in pediatric infusion rooms, thereby providing evidentiary support for the management of clinical health services.MethodsWe included children who received treatment in the pediatric infusion room of our hospital and their family members from February 2025 to May 2025. The questionnaire for family members’ medical experience was used for survey.ResultsA total of 546 family members were included. The mean score for the medical experience of these family members was 3.95 ± 1.07. Correlation analysis demonstrated that several variables were significantly associated with the medical experience scores: age of the family members (r = −0.602), their relationship with the child (r = 0.557), educational level (r = −0.577), the child's age (r = 0.622), the child's birth order (r = 0.584), and the child's type of medical insurance (r = 0.620). Further multivariate linear regression analysis confirmed that these six variables—age of the family member, relationship with the child, educational level, child's age, child's birth order, and child's medical insurance type—were independent influencing factors of the medical experience. The regression model accounted for 56.6% of the variance in the medical experience scores.ConclusionThe medical experience of family members of children in the observation and infusion department of children's hospitals still needs to be further improved. Medical workers should take appropriate measures against the relevant influencing factors to enhance their medical experience.